The validity of Keiser-M3 stationary bicycle with standard ergometer for physiological measurements associated with maximum effort - Rousseau S. Veiga; Camila B. Müller; Léo D. Cabistany; Andressa C. Formalioni; Eraldo S. Pinheiro; Fabrício B. Del Vecchio (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: This study aims to investigate the concordance between two cycle ergometers for variables measured in the test of maximum incremental effort. Methods: This correlation study enrolled 15 inactive women (19,2 ± 4,0 years old). At random, the participants performed two maximal effort incremental tests (MEIT), using cycle ergometers (Keiser-M3 and Ergo-167) on different days with a minimum interval of 72 hours. The test had stages of two minutes, and two-step increments were carried out at the end of each stage. Lactate concentration ([LAC]), and rated perceived exertion (RPE) were collected, in addition to monitoring oxygen uptake (VO2) and heart rate (HR). The Paired t-test was carried out to compare physiologic variables, Lin's test was used for correlation, and Bland Altman was used to measuring concordances among variables. Results: The correlations between physiologic parameters were considered strong for HR on the anaerobic threshold (Keiser M3 = 146 ± 14 bpm; Ergo-167 = 149 ± 9 bpm; r = 0.762), greater blood lactate value (Keiser M3 = 9,97 ± 2,51 mmol/L; Ergo-167 = 9.71 ± 2.56 mmol/L; r = 0.820), VO2max (Keiser M3 = 38,37 ± 6,97 mL/kg/min; Ergo-167 = 36.06 ± 8.4 mL/kg/min; r = 0,806) and HRmax (Keiser M3 = 186 ± 53 bpm; Ergo-167 = 188 ± 11 bpm; r = 0.716). Conclusion: The results show the feasibility of using the cycle ergometer Keiser, model M3, to perform the maximal effort incremental test, whereas there was high concordance in the physiologic responses in both ergometers for inactive women.